Application of the STAD model assisted by media share board to improve the numerical literacy of grade II students at SD Negeri 3 Jambangan Malang - Tety Nur Cholifah; Adieliyah Cahyaningsih (Jurnal Bidang Pendidikan Dasar, 2023)
The purpose of this study was to determine the application of the STAD model assisted by Shard Board media to improve students' numeracy literacy in class III fraction material at SD Negeri 3 Jambangan, Dampit District. The research used was classroom action research, the research was carried out through two cycles with steps namely Planning, Implementation, Observation, Reflection. Collecting data using research instruments required includes interviews, pretest, test, posttest, observation sheets, documentation. The results showed that the application of the STAD model assisted by Shard Board media was proven to increase students' numeracy literacy. This can be seen through cycle I getting an average of 67.5 and cycle II getting an average of 81.78. Therefore it is necessary to apply the STAD model assisted by Shard Board media when learning in class, so that it can provide variations in the learning process and can improve students' numeracy literacy.